ANALYSIS OF ISPO CERTIFICATION APPLICATION ON INDEPENDENT PALM OIL PLANTATION IN SAWIT JAYA COOPERATION AT BENTENG HULU VILLAGE, SIAK REGENCY - Rose Victoria TS; Sakti Hutabarat; Novia Dewi (Indonesian Journal of Agricultural Economics, 2018)
The ability of palm oil to produce vegetable oil with the highest oil productivity per hectare and cheaper price than other vegetable oils has made palm oil the most popular and widely consumed vegetable oil available today and can be produced throughout the year. Despite generating economic benefits, the Indonesian oil industry has been heavily criticized from within and abroad. Critics argue that the benefits of palm oil are generated at the expense of forests and forest-dependent rural communities, resulting in large greenhouse gas emissions (GHG) from land conversion and destructive habitats rich in biodiversity. The development of oil palm agribusiness should be carried out with due observance of the sustainability aspect. This study aimed to measure and compare practices undertaken in the field with ISPO (Indonesian Sustainable Palm Oil) standards. This research was conducted by collecting primary data and secondary data in the form of information and conducting interview process to self-employed oil palm smallholders. The result of the research shows that the management of independent oil palm plantation in Sawit Jaya Cooperation has not applied ISPO Certification standard. Level of application of Principles and Criteria of ISPO in self-supporting smallholders in Sawit Jaya Cooperation is still low, that is only 42% indicator that has been fulfilled